Adherence to self-care practices and associated factors among heart failure patients in Ethiopia: A systematic review and meta-analysis - Firomsa Bekele; Lalise Tafese; Addisalem Workie Demsash; Hana Tesfaye; Busha Gamachu Labata; Ginenus Fekadu (PLoS ONE, 2023)
Background Heart failure is the leading cause of hospital stays, medical expenses, and fatalities, and it is a severe problem for worldwide public health. Successful heart failure therapy requires a high level of self-care as well as devotion to different elements of the treatment plan. Despite the positive effects of heart failure self-care on health outcomes, many heart failure patients engage in insufficient self-care behaviors. Additionally, conflicting information has been found regarding the prevalence and predictors of self-care behaviors in Ethiopia. As a result, this review’s objective is to provide an overview of the most recent studies on Ethiopian heart failure patients’ self-care practices. Methods We have used four databases such as PubMed, Science Direct, Scopus and Google Scholar. Eventually, the final systematic review and meta-analysis contained eleven papers that matched the eligibility requirements. A systematic data extraction check list was used to extract the data, and STATA version 14 was used for the analysis. Heterogeneity was evaluated using the I2 tests and the Cochrane Q test statistic. To examine publication bias, a funnel plot, Egger’s weighted regression, and Begg’s test were utilized. Result The pooled magnitude of adherence to self-care was 35.25% (95%CI: 27.36–43.14). The predictors of good adherence to self-care behavior includes heart failure knowledge (odds ratio = 5.26; 95% CI, 3.20–8.65), absence of depressive symptoms (odds ratio = 3.20;95% CI,1.18–8.70), higher level of education (AOR = 3.09;95%CI,1.45–6.61), advanced New York Heart Association (NYHA) class (odds ratio = 2.66; 95% CI, 1.39–5.07), absence of comorbidity(odds ratio = 2.92; 95% CI,1.69–5.06) and duration of heart failure symptoms(odds ratio = 0.37; 95% CI, 0.24–0.58). Conclusion The extent of self-care behavior adherence is shown to be low among heart failure patients. This study showed a positive relationship between self-care behavior and factors such as proper understanding of heart failure, the absence of co-morbidity, depression, higher levels of education, a longer duration of heart failure symptoms, and advanced classes of heart failure disease. Therefore, a continuous health education should be given for patients to enhance their understanding of heart failure. Besides, special attention should be given for patients having co-morbidity and depressive symptom.